Arachne, self-care and 'power-nets' on women's self-development programmes. Issue 7 (3rd October 2022) - Fixsen, Alison; Ridge, Damien; Porter, Alan
ABSTRACT: Our article employs a feminist perspective to interpret ethnographic data on soft skills programmes (SSPs) for female staff in Higher Education (HE). We use the story of Arachne as a metaphor for how, under neoliberalism, women are instructed to create local 'nets of power, ' only to find themselves tangled in a web of conflicting expectations. Our method was informed by Institutional Ethnography (IE). Data incorporated autoethnography, participant observation, in-depth interviews with female SSP participants from academia and corporate services, as well as document study. SSPs emerged as social spaces promoting self-care and entrepreneurial practices to predominantly female audiences. An entrepreneurial self was promoted on SSPs, ostensibly to inoculate women against stress and exploitation, but arguably to perpetuate a 'super-woman' work ethic. SSPs exemplify how women are kept busy with attending to their personal 'metamorphoses' as opposed to 'meddling' in the politics of institutions, distracted from feminist agendas that might address structural gender inequalities in HE.